FAKTOR PENENTU BID-ASK SPREAD SAHAM LQ45 - Fatikhah, Sabna Ainazah; Puryandani, Siti (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jawa Tengah, 2020)
Investors always use various information to get the maximum profit in investment activities. One such information is the bid-ask spread. This study aims to determine the effect of company size, stock prices, stock price volatility and trading volume on the bid-ask spread of companies listed in the LQ45 index in the period 2015 to 2018. A total of 14 companies were taken as a purposive sampling sample in order to obtain 56 observational data. The analytical method used in this study is the method of multiple linear regression analysis. The results showed that stock prices and stock price volatility affect the bid-ask spread. While company size and trading volume do not affect bid-ask spread. Investors can consider the size of the company, stock prices, stock price volatility, and trading volume to avoid high spreads and get profit in the future.